2014
DOI: 10.1089/dna.2013.2253
|View full text |Cite|
|
Sign up to set email alerts
|

Relationships Betweenp16Gene Promoter Methylation and Clinicopathologic Features of Colorectal Cancer: A Meta-Analysis of 27 Cohort Studies

Abstract: Many existing studies have demonstrated that p16 promoter methylation might be correlated with the clinicopathologic features of colorectal cancer (CRC), but individually published results are inconclusive. This meta-analysis aimed to derive a more precise estimation of the relationships between p16 promoter methylation and the clinicopathologic features of CRC. We searched the CISCOM, CINAHL, Web of Science, PubMed, Google Scholar, EBSCO, Cochrane Library, and CBM databases from inception through August 1, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…And the patients with CRC with p16 protein negative expression would have a bigger chance of lymph node metastasis in tumor cells. And these results were consistent with the founding of Chen et al [ 76 ] They also found that p16 gene promoter hypermethylation was significantly associated with the TNM stage and Dukes stage of patients with CRC. Therefore, p16 gene promoter hypermethylation might repress the activity of p16 protein, which promoted differentiation of tumor cells and aggravated the progression of CRC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…And the patients with CRC with p16 protein negative expression would have a bigger chance of lymph node metastasis in tumor cells. And these results were consistent with the founding of Chen et al [ 76 ] They also found that p16 gene promoter hypermethylation was significantly associated with the TNM stage and Dukes stage of patients with CRC. Therefore, p16 gene promoter hypermethylation might repress the activity of p16 protein, which promoted differentiation of tumor cells and aggravated the progression of CRC.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, the status of p16 gene promoter methylation was commonly studied and significantly associated with the development of bladder cancer, lung cancer, brain cancer, and esophagus cancer. [ 72 – 75 ] At the same time, the study of Chen et al [ 76 ] has suggested that promoter hypermethylation of the p16 gene might be significantly associated with the clinicopathologic features of CRC. However, an accurate expression level of p16 gene was not detected in these studies despite the significant impact of p16 promoter hypermethylation on p16 protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to p16 expression, there is a recent metaanalysis (40), that associates various clinico-pathological features with the deregulation of its promoter via methylation. In our cohort, there is a trend towards higher p16 expression in M b-catenin (21.66 vs. 10.25 vs. 5.00, p=0.028).…”
Section: Discussionmentioning
confidence: 99%
“…The p16 INK4a protein is a cyclin-dependent kinase inhibitor that can act on cyclin-dependent kinases(CDKs) and thus inactivate the cell cycle[ 8 ].The loss of p16ink4a expression seems to be an early event in carcinogenesis. Over the past decades, the prognostic value of p16 INK4a protein has been evaluated in a wide variety of cancers [ 9 14 ].Among these, the study of Hellman et al[ 15 ] concluded that p16 INK4A expression might be used as a marker for HPV positivity in vaginal carcinoma, which shares a very similar etiology with vulvar cancer. However, its role and the etiological effect of its combination with the HPV status in vulvar cancer remain somehow unclear.…”
Section: Introductionmentioning
confidence: 99%